LEGAL TECH AND SOCIAL INCLUSION: EVIDENCE ON THE JUSTICE GAP IN THE UNITED STATES (International Seven Journal of Multidisciplinary, 2022)
The justice gap in the United States reflects the structural inability of civil and criminal legal institutions to adequately meet the legal needs of low-income and vulnerable populations. Scholarship consistently demonstrates that a substantial proportion of civil legal needs among economically disadvantaged groups remain unmet or only partially addressed. This article conducts a structured literature review examining empirical and normative research on the role of legal technology in mitigating these structural barriers. Findings indicate that digital self-help tools, AI-assisted systems, online dispute resolution (ODR) platforms, institutional interoperability mechanisms, and digital pro bono initiatives possess the potential to expand informational access, procedural efficiency, and geographic reach. However, such effects are conditional upon inclusive design, regulatory oversight, interoperability standards, public investment, and sustained digital inclusion policies. Legal technology does not operate as an automatic equalizer but as an institutional variable whose distributive impact depends on governance architecture.